Innovative liquid embolic agents based on deep eutectic solvent: Rapid gelation in situ via solvent exchange with water for endovascular embolization - Yitong Zhou; Menghui Liu; Chuandong He; Jiayuan Lin; Yanlv Chen; Mingyu Yu; Yuhan Jiang; Xin Peng (Bioactive Materials)
Current liquid embolic agents face several challenges, including poor biocompatibility and vascular recanalization. Herein, we propose an innovative liquid embolic agent composed of a coenzyme-based polymer (poly lipoic acid, PLA) and a biocompatible solvent (deep eutectic solvent, DES). The agent undergoes phase transformation to form a stable hydrogel in situ through solvent exchange with water, thereby enabling safe and effective embolization. First, DES is obtained by heating a mixture of choline chloride (ChCl) and glycerol (Gly). Subsequently, lipoic acid (LA) is incorporated into the DES and heated to produce the PLA/DES complex. Owing to the strong hydrogen bonding between the DES and PLA, the DES acts as a solvent while also inhibiting PLA depolymerization. Upon contact with blood, most of the DES exchange with water, whereas some amount of ChCl integrates within the PLA via strong hydrogen bonding. This hydrogen bonding not only prevents PLA depolymerization but also reinforces the PLA network, resulting in a stable PLA hydrogel rather than depolymerized LA monomers. Furthermore, liquid-metal (LM) nanoparticles are incorporated to fabricate radiopaque PLA/LM/DES. PLA/LM/DES shows better in vitro hemocompatibility and cytocompatibility, milder inflammatory response in a rat model, and more effective and safer embolization in a rabbit model than a commercial embolic agent (Onyx). Thus, this work provides an innovative liquid embolic agent and broadens the biomedical applications of DES.